Multi-Neuronal Recordings in the Basal Ganglia in Normal and Dystonic Rats - Baron, Mark S.; Chaniary, Kunal D.; Rice, Ann C.; Shapiro, Steven S. (Frontiers in Systems Neuroscience, 2011)
Classical rate-based pathway models are invaluable for conceptualizing direct/indirect basal ganglia pathways, but cannot account for many aspects of normal and abnormal motor control. To better understand the contribution of patterned basal ganglia signaling to normal and pathological motor control, we simultaneously recorded multi-neuronal and EMG activity in normal and dystonic rats. We used the jaundiced Gunn rat model of kernicterus as our experimental model of dystonia. Stainless steel head fixtures were implanted on the skulls and EMG wires were inserted into antagonistic hip muscles in nine dystonic and nine control rats. Under awake, head-restrained conditions, neuronal activity was collected from up to three microelectrodes inserted in the principal motor regions of the globus pallidus (GP), subthalamic nucleus, and entopeduncular nucleus (EP). In normal animals, most neurons discharged in regular or irregular patterns, without appreciable bursting. In contrast, in dystonic animals, neurons discharged in slow bursty or irregular, less bursty patterns. In normal rats, a subset of neurons showed brief discharge bursts coinciding with individual agonist or antagonist EMG bursts. In contrast, in dystonics, movement related discharges were characterized by more prolonged bursts which persist over multiple dystonic co-contraction epics. The pattern of movement related decreases in discharge activity however did not differ in dystonics compared to controls. In severely dystonic rats, exclusively, simultaneously recorded units often showed abnormally synchronized movement related pauses in GP and bursts in EP. In conclusion, our findings support that slow, abnormally patterned neuronal signaling is a fundamental pathophysiological feature of intrinsic basal ganglia nuclei in dystonia. Moreover, from our findings, we suggest that excessive movement related silencing of neuronal signaling in GP profoundly disinhibits EP and in turn contributes to sustained, unfocused dystonic muscle contractions.